Haemoglobin disorders in Australia: where are we now and where will we be in the future?. Issue 7 (July 2016) - Crighton, G.; Wood, E.; Scarborough, R.; Ho, P. J.; Bowden, D.
Abstract : Inherited disorders of haemoglobin (Hb), such as thalassaemia and sickle cell disease (SCD) are common and responsible for significant morbidity and mortality on a global scale. As Australia becomes increasingly ethnically diverse, their prevalence will increase. However, we lack important demographic and epidemiological data to manage these disorders and their consequences and to support affected individuals and communities. Thalassaemia and SCD are lifelong conditions. Affected individuals have reduced life expectancies, poorer quality of life and complex healthcare needs. Treatment strategies currently focus on prenatal diagnosis, red blood cell transfusion, iron chelation, management of iron‐related complications, haemopoietic stem cell transplantation (HSCT) and hydroxyurea. Currently, the only curative therapy is HSCT; however, gene therapy offers the possibility of cure and trials are currently underway. These therapies are associated with significant complications and substantial costs; there is also evidence of variation in approaches to diagnosis and care. Optimal strategies for many aspects of management are not yet defined and more research is necessary to inform clinical care and health service delivery.